Laparoscopic Splenectomy for Immune Thrombocytopenic Purpura (ITP) - Muhammad Arham , Jahangir Sarwar Khan , Muhammad Umer Fayyaz , Usman Qureshi , Gohar Rasheed , Usama Jalil , Salman Shafique , Sarosh Afzal Faroqui, Muhammad Arham , Jahangir Sarwar Khan , Muhammad Umer Fayyaz , Usman Qureshi , Gohar Rasheed , Usama Jalil , Salman Shafique , Sarosh Afzal Faroqui (Journal of Rawalpindi Medical College, 2018)
Background: To determine the operating time, blood loss, postoperative rise in platelet count, need of conversion to open surgery, postoperative hospital stay and postoperative complications in ITP patients undergoing laparoscopic splenectomy. Methods: In this cross-sectional study patients diagnosed with ITP undergoing laparoscopic splenectomy were included. Patient characteristics regarding operating time, blood loss, postoperative hospital stay, conversion to open surgery, postoperative complications and postoperative rise in platelet count were analyzed.. Results: Out of 23 patients, 9 were males and 14 were females. The mean age of the patients was 31±7 years. There was 1 conversion to open surgery. The mean operating time was 90±22 mins and mean blood loss 131±55 ml. 21 out of 23 (91.3%) patients showed a positive response of rise in platelet count after surgery. There was no postoperative complication in any patient. The mean postoperative hospital stay was 3±1 days. Conclusion: Laparoscopic splenectomy is associated with less operating time, postoperative hospital stay, blood loss, and postoperative complications. It produces an adequate postoperative rise in platelet count.